Why Do Romantic Relationships Start Early and End Quickly? Examining the Pattern of Unstable Relationships Among Generation Z - Péloquin , Derek; Brassard , Jessica; Saadati, Nadereh; Siegel , Lawrence; Rostami, Mehdi; Parsakia, Kamdin; Garcia , Nicole H. (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to identify and model the psychological, behavioral, and digitally mediated factors that explain why romantic relationships among Generation Z tend to initiate rapidly yet remain unstable. Methods and Materials: A cross-sectional study was conducted with a sample of Generation Z young adults residing in Toronto, Canada, all of whom had experienced at least one romantic relationship in recent years. Data were collected using a comprehensive online questionnaire assessing demographic characteristics, relationship histories, attachment-related variables, emotional regulation, and digital relational practices such as dating-app use and social media monitoring. A machine learning framework was employed to analyze the data, including supervised classification algorithms and unsupervised clustering techniques. Multiple models were trained and validated using cross-validation procedures, and explainability methods were applied to identify the most influential predictors of relationship instability. Findings: Inferential results indicated that non-linear machine learning models significantly outperformed linear models in predicting relationship instability. Rapid emotional attachment, attachment anxiety, fear of abandonment, intensive dating-app use, and frequent social media monitoring emerged as the strongest predictors of unstable romantic trajectories. Clustering analyses revealed distinct relational profiles, including accelerated–fragile, digitally entangled, avoidant–episodic, and relatively stable patterns, with the majority of participants falling into instability-prone profiles. Protective effects were observed for indicators of secure attachment and offline relational support. Conclusion: The findings demonstrate that unstable romantic relationships among Generation Z are best understood as outcomes of interacting psychological vulnerabilities and digitally shaped relational practices rather than isolated individual deficits. Early emotional acceleration combined with constant digital comparison creates conditions under which relationships form quickly but lack durability.